2013
DOI: 10.3390/antiox2040293
|View full text |Cite
|
Sign up to set email alerts
|

Saffron: A Natural Potent Antioxidant as a Promising Anti-Obesity Drug

Abstract: Obesity is associated with various diseases, particularly diabetes, hypertension, osteoarthritis and heart disease. Research on possibilities of herbal extracts and isolated compounds from natural products for treating obesity has an upward trend. Saffron (Crocus Sativus L. Iridaceae) is a source of plant polyphenols/carotenoids, used as important spice and food colorant in different parts of the world. It has also been used in traditional medicine for treatment of different types of illnesses since ancient ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 67 publications
0
102
0
1
Order By: Relevance
“…Saffron extracts and its bioactive constituents have been demonstrated to possess excellent antioxidant properties (Hosseinzadeh et al, 2009;Karimi et al, 2010;Mashmoul et al, 2013). Further, their memory and learning enhancing properties in animal models have been attributed to their antioxidant action (Papandreou et al, 2006(Papandreou et al, , 2011Amin and Hosseinzadeh, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Saffron extracts and its bioactive constituents have been demonstrated to possess excellent antioxidant properties (Hosseinzadeh et al, 2009;Karimi et al, 2010;Mashmoul et al, 2013). Further, their memory and learning enhancing properties in animal models have been attributed to their antioxidant action (Papandreou et al, 2006(Papandreou et al, , 2011Amin and Hosseinzadeh, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Research results have shown that they are also capable of inhibiting enzymes related to fat metabolism, including pancreatic lipase, lipoprotein lipase, and glycerophosphate dehydrogenase [132]. Although research about the connection between saffron compounds and body weight is not definitive yet, there are several theories that saffron has a potential to combat against overweight/obesity and related metabolic disorders owing to its high antioxidant activity and different biological properties [133].…”
Section: Therapeutic Benefits Of Saffronmentioning
confidence: 98%
“…This antagonistic effect at central NMDA receptors leads to an inhibition of postsynaptic potentials and inhibition of glutamatergic transmission, as recently shown in rat cortical brain (Berger et al 2011). Besides the antidepressive effects saffron extracts and especially its main secondary metabolite crocin has been used for the treatment of coronary diseases (for review see Kamalipour et al 2011;Joukar et al 2010) due to its potential antihyperlipidemic effects (Lee et al, 2005), inhibition of cardiac Ca 2+ channels (Boskabady et al 2008) and pronounced antioxidant reactivity (Mashmoul, 2013), Main secondary metabolites of saffron extracts are about 0.5% of volatile compounds with safranal as main constituent (Schmidt et al 2007;Lechtenberg et al 2008). The typical spicy taste of saffron originates from picrocrocin (5-15%), the biosynthetical precursor of safranal.…”
Section: Introductionmentioning
confidence: 94%